2021
DOI: 10.3390/risks9110194
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Hotels’ Dynamic Capability under the Risks of COVID-19

Abstract: The effects of COVID-19 on tourism are irreversible, with potential reductions in income, job losses, shifting working landscapes, and visible health-related fears. These adversities are reinforced in the hospitality business, particularly for hotels, the income streams of which rely on individual movements. This study investigates the process undertaken by the hotel industry in Indonesia to face the current challenges, particularly in terms of the dynamic capabilities possessed by hotel businesses. This const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 138 publications
(127 reference statements)
2
8
0
Order By: Relevance
“…Losses in the food and beverage sector are estimated at 1,748.54 million USD to 1,899.45 million USD. This result is in line with Amar et al (2021) and Laksito and Yudiarta (2021) that COVID-19 has had a tremendous impact on the decline in the tourism sector. This impact is felt very deeply by business actors, especially MSMEs engaged in the tourism sector (Amar et al, 2021;Laksito & Yudiarta, 2021;Nursjanti & Amaliawati, 2021).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Losses in the food and beverage sector are estimated at 1,748.54 million USD to 1,899.45 million USD. This result is in line with Amar et al (2021) and Laksito and Yudiarta (2021) that COVID-19 has had a tremendous impact on the decline in the tourism sector. This impact is felt very deeply by business actors, especially MSMEs engaged in the tourism sector (Amar et al, 2021;Laksito & Yudiarta, 2021;Nursjanti & Amaliawati, 2021).…”
Section: Resultssupporting
confidence: 90%
“…This result is in line with Amar et al (2021) and Laksito and Yudiarta (2021) that COVID-19 has had a tremendous impact on the decline in the tourism sector. This impact is felt very deeply by business actors, especially MSMEs engaged in the tourism sector (Amar et al, 2021;Laksito & Yudiarta, 2021;Nursjanti & Amaliawati, 2021). This is natural because Indonesia anticipates the spread of COVID-19 with a lockdown or Large-Scale Social Restrictions/PSBB.…”
Section: Resultssupporting
confidence: 90%
“…resources, capabilities, and structure) that enable the adoption of digital technologies. The first important factor is the infrastructure, including physical ones, technological capabilities, and financial resources ( Amar, Syariati, Ridwan and Parmitasari, 2021 ; Van et al, 2020 ). Studies showed that the hotel’s infrastructure and IT capabilities act as a supportive environment for innovation and the use of innovative mobile technology ( Amar et al, 2021 ; Han, Lee, Edvardsson and Verma, 2021 ; Lin, Chen, Yin, Li, Zhu and Luo, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As observed by Marome and Shaw [4], the businesses in the service and tourism sector that account for a large proportion of jobs became financially insecure during COVID-19. A robust decline in the demand experienced by the tourism industry during the peak season of 2020 persuaded business organizations to respond through large-scale employee lay-offs [3,8,38,41,42]. With an enormous fall in tourism demand resulting from lockdowns and border closures, the pandemic has affected the well-being of local communities that majorly depended on tourism for their livelihood [15,43].…”
Section: Covid-19 and The Responses Of The Tourism Industrymentioning
confidence: 99%
“…The torment caused by the pandemic calls for transformative decisions of tourism practitioners and policymakers to reactivate tourism sustainably [5,35,65] within the framework of innovations and creativity [23,26,41,71]. Transformational change should not only focus on finding a solution for socio-economic crises posed by COVID-19, but various political, social, and market players also need to contemplate further innovations, investments, and efforts to realize a climate-neutral world in a post-pandemic era [72].…”
Section: Tourism Sustainability In the Post-covid-19 Era Big Challeng...mentioning
confidence: 99%